Promoting the psychosocial and communication aspects of nursing care quality using time management skills training - Jamileh Farokhzadian; Sakineh Miri; Mahboobe Doostkami; Zahra Rezahosseini; Parvin Mangolian Shahrbaaki (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Although using time management skills is a major component of nursing professional practice, they have not received much attention. Time management training can improve the psychological and communication aspects of nursing care quality. Therefore, this study aimed to evaluate the effect of time management skills training on the psychosocial and communication aspects of nursing care quality. MATERIALS AND METHODS: This semi-experimental study was conducted at Valiasr Hospital of Shahr Babak City, Kerman Province, in the Southeast of Iran, during 2018. The study population consisted of 100 nurses who were randomly assigned to one of the two groups: an intervention group or a control group. To identify and measure the outcomes, nurses' perceptions of the psychosocial and communication aspects of care quality were first assessed by the Quality Patient Care Scale (Qualpacs) at pretest. Then, the intervention group received the 2 days of training on time management skills for 12 h. The posttest outcome data were collected from both the groups 1 month after the intervention. RESULTS: No statistically significant differences were observed between the two groups with respect to the total mean scores of nursing care quality and its psychosocial and communication aspects before the intervention (t = 1.96, P = 0.09). However, there was a statistically significant difference between the two groups in this regard after the intervention, and the mean nursing care quality scores and its related aspects were improved in the intervention group (t = 5.76, P < 0.0001). CONCLUSIONS: The time management skills training could significantly improve psychosocial and communication aspects of nursing care quality. Health-care managers should allocate facilities to clinical training programs so that health-care professionals can acquire the time management skills. The higher effectiveness of time management training can be determined by its application in diverse domains of health care.